Influence of calcium ions on alcohol strees responses of Saccharomyces cerevisia - Iman H. Katte; Nibal Kh. M; F. J. Shalesh; F. R. Ali; Sana’a Kh. M (Journal of Madenat Alelem University College, 2011)
Bioethanol is an important industrial chemical with emerging potential as a biofuel to replace fossil fuels. The yeast Saccharomyces cerevisiae is commonly used for ethanol production. The limited ethanol tolerance of the yeast results in low productivity .This search come to evaluate different levels of calcium ions in response to ethanol stress of yeast S. cerevisiae, which isolated from different local sources. The minimal inhibitory concentration and Lethal concentration of the isolates was evaluated by exposure to different concentration of ethanol, the resistant isolates to higher concentration 8% ethanol were selected. Growth determent by optical density at 600 nm to incubator period 24,48,72 h with ethanol 8%. Selected isolates which appeared best growth in deferent incubator period to experiments of addition different levels of calcium ions as calcium chloride .concentration (1-1.2mM) have positive effect to growth of yeast Saccharomyces cerevisiae .and tolerance to alchol strees the isolates deffernt between them in evaluate the optimal concentration to make positive effect in rang (0,8 – 1,6 mM) .